Environmental Risk Factors for Sarcoidosis - Judson, Marc A. (Frontiers in Immunology, 2020)
Sarcoidosis is a multisystem granulomatous disease that may affect any body organ. Sarcoidosis is associated with many environmental and occupational exposures. Because the exact immunopathogenesis of sarcoidosis is unknown, it is not known whether these exposures are truly causing sarcoidosis, rendering the immune system more susceptible to the development of sarcoidosis, exacerbating subclinical cases of sarcoidosis, or causing a granulomatous condition distinct from sarcoidosis. This manuscript outlines what is known about the immunopathogenesis of sarcoidosis and postulates mechanisms whereby these exposures could cause or exacerbate the disease. We also describe the varied environmental and occupational exposures that have been associated with sarcoidosis. This includes potential infectious exposures such as mycobacteria and Propionibacterium acnes, a skin commensal bacterium, as well as non-infectious environmental exposures including inhaled bioaerosols, metal dusts and products of combustion. Further insights concerning the relationship of environmental exposures to the development of sarcoidosis may have a major impact on the prevention and treatment of this enigmatic disease.